Henryk Sienkiewicz i artyści. "Ogniem i mieczem" w interpretacji plastycznej Juliusza Kossaka i Antoniego Piotrowskiego = Henryk Sienkiewicz and the artists. Visual interpretation of the novel "With Fire and Sword"["Ogniem i mieczem"] by Juliusz Kossak and Antoni Piotrowski - Pijanowska, Kamila (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The novel "With Fire and Sword" by Henryk Sienkiewicz was published in the years 1883-1884 in newspapers "Słowo" ["The Word"] and "Czas" ["The Time"]. It gained popularity among the readers and became a growing inspiration for the artists. Even before the publication of the novel was complete, the first works referring to its plot appeared. One example can be the drawing by Jan Rosen showing Jan Skrzetuski in despair on the ruins of the Rozłogi manor.
Keywords: Sienkiewicz, Henryk (1846-1916); Kossak, Juliusz (1824-1899); Piotrowski, Antoni Adam (malarz; 1853-1924); "Ogniem i mieczem"; ilustracja książkowa; book illustration